The International Encyclopedia of Anthropology 2018
DOI: 10.1002/9781118924396.wbiea1496
|View full text |Cite
|
Sign up to set email alerts
|

WorldHealthOrganization (WHO)

Abstract: An overview is presented of the rationale, design, and analysis plan for the WMH-CIDI clinical calibration studies. As no clinical gold standard assessment is available for the DSM-IV disorders assessed in the WMH-CIDI, we adopted the goal of calibration rather than validation; that is, we asked whether WMH-CIDI diagnoses are 'consistent' with diagnoses based on a state-of-the-art clinical research diagnostic interview (SCID; Structured Clinical Interview for DSM-IV) rather than whether they are 'correct'. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Lacson (2010) explained that CKD patients experienced a decrease in quality of life, including physical, mental, and social well-being [17]. The World Health Organization Quality of Life states that quality of life is an individual's perception of abilities, limitations, symptoms, and psychosocial characteristics of life in the context of culture and value systems to carry out their roles and functions [18]. Research conducted by Sathvik et al (2008) in a healthcare unit in India using WHOQOL-Brief showed that the quality of life for healthy individuals or kidney transplants is much better than patients undergoing HD [19].…”
Section: Quality Of Life In For Patients With Chronic Kidney Failurementioning
confidence: 99%
“…Lacson (2010) explained that CKD patients experienced a decrease in quality of life, including physical, mental, and social well-being [17]. The World Health Organization Quality of Life states that quality of life is an individual's perception of abilities, limitations, symptoms, and psychosocial characteristics of life in the context of culture and value systems to carry out their roles and functions [18]. Research conducted by Sathvik et al (2008) in a healthcare unit in India using WHOQOL-Brief showed that the quality of life for healthy individuals or kidney transplants is much better than patients undergoing HD [19].…”
Section: Quality Of Life In For Patients With Chronic Kidney Failurementioning
confidence: 99%